A Review of Perioperative Complications of Outpatient Total Ankle Arthroplasty. (February 2018) - Borenstein, Todd R.; Anand, Kapil; Li, Quanlin; Charlton, Timothy P.; Thordarson, David B.
Background: Total ankle arthroplasty (TAA) is commonly pursued for patients with painful arthritis. Outpatient TAA are increasingly common and have been shown to decrease costs compared to inpatient surgery. However, there are very few studies examining the safety of outpatient TAA. In this study, we retrospectively reviewed 65 consecutive patients who received outpatient TAA to identify complication rates. Methods: The medical records of 65 consecutive outpatient TAA from October 2012 to May 2016 with a minimum 6-month follow-up were reviewed. All patients received popliteal and saphenous blocks prior to surgery and were managed with oral pain medication postoperatively. All received a STAR total ankle. Demographics, comorbidities, American Society of Anesthesiologists (ASA) class, and perioperative complications including wound breakdown, infection, revision, and nonrevision surgeries were observed. Mean follow-up was 16.6 ± 9.1 months (range, 6-42 months). Results: There were no readmissions for pain control and 1 patient had a wound infection. The overall complication rate was 15.4%. One ankle (1.5%) had a wound breakdown requiring debridement and flap coverage. This patient thrombosed a popliteal artery stent 1 month postop. The 1 ankle (1.5%) with a wound infection occurred in a patient with diabetes, obesity, hypertension, and rheumatoid arthritis. Conclusion: This study demonstrates the safety of outpatient TAA. The combination of regional anesthesia and oral narcotics provided a satisfactory experience with no readmissions for pain control and 1 wound infection. The 1 wound breakdown complication (1.5%) was attributed to arterial occlusion and not outpatient management. Level of Evidence: Level IV, retrospective case series.